2005
DOI: 10.1097/01.gco.0000183530.03481.64
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating occult incontinence

Abstract: Minimal existing evidence in the English language suggests that patients with occult incontinence are at increased risk of POSUI. Outcomes in occult incontinence patients undergoing repair of pelvic organ prolapse need systematic study. Until there is adequate solid evidence on the predictive values of our screening test, we cannot counsel patients regarding our ability to prevent POSUI or protect them from unnecessary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 31 publications
0
29
0
4
Order By: Relevance
“…Occult SUI occurs in 11-22% of patients after POP surgery [18]; in this study, de novo SUI rate was 20% and most of these patients needed surgery for SUI later on. Six patients underwent concomitantly an anti-incontinence operation ( Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…Occult SUI occurs in 11-22% of patients after POP surgery [18]; in this study, de novo SUI rate was 20% and most of these patients needed surgery for SUI later on. Six patients underwent concomitantly an anti-incontinence operation ( Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…However, according to that study, there is no evidence to perform a prophylactic anti-incontinence procedure on women with OSUI. 27 Liang et al reported that none of their 30 patients who did not have OSUI during pessaryreduced urodynamic trial, developed POSUI. They concluded that concomitant anti-incontinence surgery is not necessary in this group.…”
Section: Discussionmentioning
confidence: 99%
“…However, during surgery to reduce the prolapsed uterus or anterior vaginal wall it may be noted from the urodynamic study that 36 to 80% of the women with pelvic organ prolapse have coexisting urodynamic stress incontinence. These patients have occult stress urinary incontinence (Haessler et al, 2005;Reena et al, 2007). In addition, postoperative stress urinary incontinence (de novo stress urinary incontinence) has been noted in 10 to 30% of women following prolapse repair (Bump et al, 1996;Hung et al, 2004;Reena et al, 2007).…”
Section: Prevalence Of Pelvic Organ Prolapse Associated Stress Urinarmentioning
confidence: 99%